The Theoretical Study of Unexpected Magnetism in 2D Si-Doped AlN - Wan, Wenhui; Kang, Na; Ge, Yanfeng; Liu, Yong (Frontiers in Physics, 2022)
In this paper, the structural and magnetic properties of Si-doped bulk and 2D AlN were systematically investigated by first-principles calculations. Si atom prefers to substitute Al atom in both bulk and 2D AlN under N-rich growth conditions. In bulk AlN, Si dopant exhibits a non-magnetic state, a uniform distribution, and a strong anisotropic diffusion energy barrier. Contrast with that, Si dopant prefer to form a buckling structure and exhibits a magnetic moment of 1 μ_B in 2D AlN. At a low Si concentration, Si atoms tend to get together with antiferromagnetic coupling between each other. However, the magnetic coupling among Si atoms changes to ferromagnetic coupling as Si concentration increases, due to the enhanced exchange splitting and delocalized impurity states. At the extreme doping limit, monolayer SiN along with its analogs GeN and SnN are ferromagnetic semiconductors with a large band gap and a high curie temperature. These results indicate that 2D AlN doped by group-IV atoms has potential applications in spintronic devices.